An electrochemical investigation on the mechanisms of interfacial interactions of a xanthate collector on PGM surfaces in the presence of ions - Dzinza, Lucia (Department of Chemical Engineering, 2023)
Water is a vital transport and process medium used in mineral processing. Fresh water is substantially utilized as an ideal flotation media in the froth flotation process (Rao et al., 2016). However, the mining sector is impelled to save on the consumption of fresh water and reduce waste discharge owing to limited freshwater supply (Ridoutt and Pfister, 2010), stringent environmental regulations (Amezaga et al., 2011) and the increase in water demand among multiple users (Rijsberman, 2006). To improve water efficiency, the use of impure primary water supplies, and process water recycling has been implemented in flotation circuits. Generally, the recycling of process water is executed from tailings dams, thickener overflows, and dewatering and filtration units. The recycling of process water has been considered to be advantageous as it reduces freshwater consumption, lowers waste discharge and reduces volumes of reagents required in flotation circuits (Muzenda, 2010). However, recycled process water has been found to exhibit increased concentrations of typical contaminants such as colloidal matter, metal ions, sulphates, sulphites, thiosalts, calcium, magnesium, sodium, potassium, and residual floatation reagents. These contaminants affect the process water quality, which plays a vital role in flotation efficiency. Though a significant amount of work has been done on the effects of water quality on the flotation of valuable minerals, many studies have focussed on base metal sulphides and the use of benchscale techniques. Literature speculates that ions in process water hinder the interaction between xanthate collectors and valuable minerals, hence, contributing to a decrease in flotation recoveries (Kirjavainen et al., 2002, Boujounoui et al., 2015). The findings in literature have been deduced without an understanding of the underlying mechanisms of interaction between xanthate collectors and mineral surfaces in the presence of ions. Accordingly, literature still holds a lack of understanding on how ions affect the adsorption of xanthate collectors on mineral surfaces. This study, therefore, seeks to unpack the underlying mechanisms of interfacial interactions between ions with PGMs and the subsequent adsorption kinetics of a xanthate collector. This study investigated the effects of Ca2+, Mg2+, SO4 2- , S2O3 2- and Na+ ions at increasing ionic strength, on the adsorption of SIBX on synthetic PdS and PdTe2 minerals. The selection of the minerals was based on the need to give an insight into the differences in reactivities of the very floatable minerals (PdS) and the difficult-to-float minerals (PdTe2), with SIBX in the presence of ions. The mechanisms in question were examined by electrochemical techniques at laboratory scale. Rest potential measurements were used to determine the interactions of ions and/or SIBX on the PGM surfaces. Cyclic voltammetry was employed to determine the redox reactions that occur on the PGM surfaces in the absence and presence of ions and SIBX. Ultimately, electrochemical impedance spectroscopy was used to demonstrate the adsorption mechanisms of SIBX in the absence and presence of the investigated ions. The rest potential measurements generally displayed an increase in the extent of interactions between the investigated ions with the palladium minerals, with an increase in ionic strength. An inverse relationship was exhibited on the extent of interactions between the ions and PdS, and the extent of interaction between SIBX and PdS. Divalent ions displayed higher interactions with the palladium minerals than the monovalent ions investigated. All salts were found to demonstrate a decrease in the rest potential for PdS at all concentrations except for MgSO4, which increased the rest potential at 5 SPW and 10 SPW. Final rest potentials for most conditions were observed to be above the equilibrium potential of dixanthogen formation except for Na2S2O3 at 3 SPW, 5 SPW and 10 SPW, and CaCl2 at 1 SPW. Dixanthogen formation was most likely favoured on PdS for the conditions with final rest potentials above the equilibrium potential of dixanthogen formation. With regard to the PdTe2 mineral, it was found that most ions enhanced the interaction between SIBX and PdTe2. Contrary to the findings of PdS, it was found that most salts exhibited an increase in rest potential on PdTe2 except for Na2S2O3. Final rest potentials for all conditions investigated were observed to occur above the equilibrium potential of dixanthogen formation except for Na2S2O3 at all ionic strengths, MgCl2 at 10 SPW and NaCl at ionic strengths of 3 SPW, 5 SPW and 10 SPW. The latter conditions show that the formation of a metal-xanthate on PdTe2 was favoured. Generally, for both minerals, NaCl displayed the least interaction. It was found that increasing the ionic strength of salts, generally decreased the rate of dixanthogen formation on PdS. On the contrary, SIBX interacted more with PdTe2 at an increase in the ionic strength of salts. This observation favoured the formation of either a metal-xanthate or dixanthogen at a slower rate. Additionally, it was determined that the adsorption of ions investigated occurred via interfacial charge transfer kinetics, where an ion exchange mechanism has been proposed in the case of the divalent anions. In the case of divalent cations, it was presumed that the ions dissociate in solution and precipitate upon their interaction with the palladium minerals to hydroxides and/or carbonates. This study has shown that the mechanism of adsorption of ions on palladium minerals is heavily influenced by the type of mineral surface onto which the ions adsorb. The extent of interaction of ions with palladium minerals together with their corresponding oxidation products can be determined by the mineral type and the salt type and its ionic strength. Moreover, it was denoted that an electrochemical system that consists of salts at the palladium mineral surfaces can best be described by a resistor, Rs in series with a parallel circuit of a capacitor, Cdl, representing the electrical double layer and a resistor indicating Rct. For an electrochemical system with both salt and SIBX, it has been surmised that an equivalent circuit consisting of a resistor, Rs, in series with a parallel circuit of a capacitor, Cc, representing a coating layer formed on the palladium surfaces as a result of the adsorption and oxidation od SIBX and a capacitor, Cdl. This work has shown that the mechanisms of interactions between xanthates and PGMs in the absence and presence of salts can be successfully determined using electrochemical techniques. An understanding of such mechanisms developed from the interactions of Ca2+, Mg2+, SO4 2- , S2O3 2- and Na+ ions with SIBX on PGM minerals will help alleviate flotation problems caused by the troublesome ions. An understanding of the mechanisms proposed by this study will act as a diagnostic tool for developing flotation strategies that will maximize flotation recoveries where water quality is concerned